2016
DOI: 10.2355/isijinternational.isijint-2016-044
|View full text |Cite
|
Sign up to set email alerts
|

Silico-ferrite of Calcium and Aluminum Characterization by Crystal Morphology in Iron Ore Sinter Microstructure

Abstract: Correct identification of mineral phases in iron ore sinters is key for further research, in which individual sinter properties are derived directly from mineral phases. Nowadays widespread image analysis and techniques based on the visual quantification may not exactly evaluate mineral type, what has an unfavorable effect on the overall phase analysis and all functions derived from it. Some specifics were demonstrated by microscopic examination of sinter samples and pointing out differences in calcium ferrite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…It has been assumed that prismatic and platy SFCA correspond to SFCA and SFCA-I, respectively, but based on this evidence, it appears that PC is under-representing the proportion of SFCA-I present. Traditionally, morphologies are used to distinguish these two variants when using optical-based techniques; however, recent work by Mezibricky and Frolichova [5] has demonstrated that using a morphological approach to distinguish between SFCA and SFCA-I types is problematic since both phases can exhibit similar textures.…”
Section: As Shown Inmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been assumed that prismatic and platy SFCA correspond to SFCA and SFCA-I, respectively, but based on this evidence, it appears that PC is under-representing the proportion of SFCA-I present. Traditionally, morphologies are used to distinguish these two variants when using optical-based techniques; however, recent work by Mezibricky and Frolichova [5] has demonstrated that using a morphological approach to distinguish between SFCA and SFCA-I types is problematic since both phases can exhibit similar textures.…”
Section: As Shown Inmentioning
confidence: 99%
“…Murao et al [27] determined thermodynamic stability for SFCA, and this range is reproduced in Figure 6. Less work has been reported for SFCA-I; however, many authors have reported a difference in the chemical composition of SFCA and SFCA-I [3,5,7,28]. Selected results are plotted in Figure 6 for comparison.…”
Section: Semmentioning
confidence: 99%
See 1 more Smart Citation
“…The objective of the synthesis was to prepare pure prismatic SFCA crystals, i.e., without any intergrowing SFCA-I crystals, which would make the evaluation of indentation erroneous. It is known from the literature that SFCA-I does not crystalize from the melt [26,27]. Thus, to prevent the formation of SFCA-I, the thermal treatment was chosen to ensure complete melting of the ferrites which had formed through solid-state reactions during the early stages of the experiment.…”
Section: Mixturementioning
confidence: 99%
“…Nowadays, the research in the field of iron ore sinter mineralogy is concentrated on one group of the bonding phases -complex calcium ferrites (designated as SFCA, an acronym for silicoferrite of calcium and aluminum), which accumulate besides Fe2O3 and CaO also SiO2, Al2O3 and other minority components [3][4][5]. In industrially produced sinters, there are 2 types of SFCA-s according to the chemical composition: low-Fe SFCA and high-Fe SFCA-I [6]. Before advanced study of SFCA/SFCA-I, calcium ferrites CaFe4O7 and CaFe3O5 were considered as the main ferrite phases in lime-fluxed iron ore sinters [7,8].…”
Section: Introductionmentioning
confidence: 99%